Introducing the Power In Nepali Girls (PING) empowerment scale - Jessica Griffin Burke; Sara E. Baumann; Ariel Shensa; Niva Joshi; Jennifer R. Jones; Pema Lhaki (Taylor & Francis Group, 2023)
ABSTRACTThe multi-dimensional concept of empowerment is context specific, uniquely defined in various cultures, and challenging to measure. The aim of this study was to develop a scale for measuring empowerment among adolescent girls in Nepal. Twenty-nine items related to empowerment were drawn from formative, participatory research conducted in southern Nepal to comprise a draft empowerment scale. A case/control survey among 300 adolescent Nepali girls was then conducted to refine the scale. Factor analysis determined the most parsimonious scale and identified the underlying structure of items, resulting in the The Power In Nepali Girls (PING), a two-factor, 16-item empowerment scale. Factor 1 items address decision-making power and treatment in family and society. Factor 2 items address knowledge, education, and skills development. We used the 16-item scale to assess the impact of a social and financial skills program on empowerment among adolescent girls residing in southern Nepal. The PING scale is a culturally- and population-specific measure that can be used to quantify the impact of empowerment programs in Nepal among adolescent girls. The methods used also serve as a template for future work aiming to design context-specific measures of empowerment using community-engaged approaches.